Initial growth of Mansoa alliacea (Bignoniaceae), species of interest in the Amazon region of Ecuador - Abril, R. Vinicio; Ruiz, T.; Alonso, Jatnel; Cabrera, Génova (Cuban Journal of Agricultural Science, 2017)
In order to know the growth characteristics of Mansoa alliaceae, the initial growth up to 320 days were recorded, from the appearance of the shoot in the height of the plant, stem diameter, in which linear and nonlinear models were evaluated. The number of leaves and branches length was recorded, in which analysis of variance was applied for the different sampling times. It was also determined whether precipitation influenced growth. Linear models presented better fit for plant height and shoot diameter. Green leaves predominated, which showed significant differences in all sampling times. The branches length was different for the different times. It is concluded that the species did not stop its growth during the first 320 days after planting. The emission and branches growth and the number of leaves were also important elements of growth. Key words: height, diameter of the plant, number of leaves